Brain Plasticity and the Labbé Procedure: Where do we stand? - Zhen Yu Wong; Jeremias Schmidt; Frank W. de Jongh; Koen J.A.O. Ingels; Niels van Heerbeek; Sjaak Pouwels (JPRAS Open)
ABSTRACT: The Labbé procedure is a recognised technique for facial reanimation in patients with facial paralysis (FP). Although it was initially believed that brain plasticity plays a crucial role in the success of this procedure, the evidence supporting this mechanism is limited. This review provides an overview of brain plasticity and its potential application in the Labbé procedure. Additionally, the possibility of trigeminal-facial neurotisation as an alternative mechanism is discussed. Further research is needed to explore the mechanisms to improve the treatment options and enhance early rehabilitation for individuals with FP.